APPLICATION OF E-MARKETING IN ENTREPRENEURSHIP LEARNING FOR STUDENT WITH INTELLECTUAL DISABILITY - Edi Purwanta; Hulfa Hulfa (Jurnal Cakrawala Pendidikan, 2018)
Abstract:Entrepreneurship learning is a process that equips students in developing their soul, attitude, and carefulness in seeing opportunities and organizing the sustainability of a business. This study set out to investigate the effect of e-marketing towards the understanding of marketing in entrepreneurship learning of senior high school students with mild intellectual disability through e-marketing. A quantitative approach with one group pretest-posttest design was used in this study. A total of 24 students with mild intellectual disability from three schools in Magelang and Temanggung Regency participated in this study. A purposive sampling was applied in selecting these senior high school students. The data in this study were collected through a test. Anon-parametric statistical analysis technique, i.e. Wilcoxon sign rank test, was used to analyze the data. Based on data analysis performed, the calculated Z value is -4.115 with Asymp.Sig (2-tailed) 0.000 at significant (α) 0.05 level. The results indicated that the students mean score after the treatment was significantly higher than their average score before the treatment. It is then concluded that the application of e-marketing has an effect in improving the understanding of marketing in entrepreneurship learning of senior high school students of with mild mental disability. Keyword:e-marketing, entrepreneurship learning, intellectual disability PENERAPAN E-MARKETING DALAM PEMBELAJARAN KEWIRAUSAHAAN SISWA TUNAGRAHITA RINGAN TINGKAT SMA Abstrak: Pembelajaran kewirausahaan merupakan pembelajaran yang membekali siswa dalam mengembangkan jiwa, sikap, kejelian dalam melihat peluang dan pengorganiasasian dalam keberlangsungan suatu usaha. Penelitian ini bertujuan untuk mengetahui pengaruh e-marketing terhadap pemahaman pemasaran dalam pembelajaran kewirausahaan siswa tunagrahita ringan tingkat SMA melalui e-marketing.Penelitian menggunakan pendekatan kuantitatif dengan desain one group pretest-posttest. Subjek penelitian berjumlah 24 siswa tunagrahita ringan dari tiga sekolah di tiga kota yang berbeda yakni Magelang, and Temanggung. Sampel diambil secara purposif, yaitu siswa yang berada di tingkat SMA.Teknik pengumpulan data menggunakan tes.Analisis data menggunakan teknik analisis statistic nonparametric Wilcoxon sign rank test. Berdasarkan analisis data yang dilakukan, diperoleh nilai Z adalah -4,115 dengan Asymp.Sig (2-tailed) 0,000 pada taraf signifikan (α) 0,05. Hasil dari penelitian menyatakan bahwa nilai rata-rata sesudah diberikan perlakuan lebih tinggi secara signifikan daripada hasil nilai rata-rata sebelum diberikan perlakuan.Hal itu dapat disimpulkan bahwa penerapan e-marketing berpengaruh meningkatkan pemahaman pemasaran dalam pembelajaran kewirausahaan siswa tunagrahita ringan tingkat SMA. Kata kunci: e-marketing,pembelajarankewirausahaan, tunagrahita